Mortuus est… in and in Greater Poland region - Prałat, Emilian (Requiem, 2025)
The objective of the following article is to present several aspects of death and burial practices in Greater Poland region. The first type of death to be discussed in the article is suicide, which presents itself as not obvious (in the sense of informing the public about it, and thus its influence on the funeral ceremony) yet difficult. The commemoration of suicidal death will be discussed on the example of Zofia Kozmian. Another important type of burial rituals addressed in this study are the funerals of national heroes such as Dezydery Chłapowski and Edmund Taczanowski, whose sepulchral sites represent a different character (and consequently meaning attached to such tombs). For the purpose of presenting this type of commemoration the result of the investigation of the Chlapowski crypt, which took place during the revitalization of the family necropolis in Rąbiń near Krzywiń (between 2020-2023), will be included in the analysis. Finally, the case of Taczanowski will be explored to exemplify the theatrum accompanying the transfer of the remains and the reburial ritual at Powązki was discussed. Based on unpublished source materials and analytical research, it is possible to refer to the specificity of the funeral tradition in Greater Poland, as well as to present several different cases, including the burials of national heroes, as well as family tragedies and the related complicated experience of both trauma and the trauma itself.